Dual COX-2/5-LOX inhibitors from Zanthoxylum simulans inhibit gastric cancer cells by cross-mediating thyroid, estrogen, and oxytocin signaling pathways - Tian, Yong-Qiang; Liu, Jing; Cheng, Peng; Zou, Jian; Xu, Hui-Fang; Shi, Xin-Hua; Zhang, Yi-Sheng; Mei, Ling (Frontiers in Chemistry, 2024)
Cyclooxygenase 2 (COX-2) and 5-lipoxygenase (5-LOX) are overexpressed in gastric cancer, dual inhibitors of which exhibit potential against metastasis and invasion with less side effects. To discover inhibitors targeting COX-2 and 5-LOX, we conducted ultrafiltration and enrichment calculation to screen candidates in quaternary alkaloids (QAs) from Zanthoxylum Simulans through LC and LC-Q-TOF. For intensive peaks, peak 19 (berberine) and 21 (chelerythrine) were observed as the most potent dual candidates and showed selective affinity to 5-LOX over COX-2. Peak 19 showed an enrichment at 4.36 for COX-2 and 22.81 for 5-LOX, while peak 21 at 7.81 for COX-2 and 24.49 for 5-LOX, respectively. Molecular docking results revealed chelerythrine as a better dual inhibitor, showing timeand dose-dependent anti-proliferation against AGS cells. Bio-informatics strategies, GEO, GO and KEGG, suggested that hormone pathways in gastric cancer might be mediated by chelerythrine. Further reviews and summaries helped to outline the mechanisms by which COX-2/5-LOX inhibitors might promote apoptosis in gastric cancer cells via estrogen, thyroid and oxytocin signaling pathways. Chelerythrine was also adopted to gastric cancer cells to verify the regulation of these three signaling pathways. As a result, significantly calling back of TSHR, TRα3 and TRβ1 and suppressing ER-α36-Src could benefit the anti-proliferation of chelerythrine. However, it was disappointing that regulation of ER-α66, ER-β and OTR contributed inversely negative effects on anti-gastric cancer cells. At present, the integrative study not only revealed cheleythrine as the most potent dual COX-2/5-LOX inhibitor from QAs, but also generally highlighted that comprehensive regulation of estrogen, thyroid and oxytocin pathway should be noted once gastric cancer cells were treated with inflammatory inhibitors.